Reducing peak thermo-electricity energy demand in building: Insights from sensible and latent storage – Applicable in hot and arid regions - Wajdi Rajhi; Noreen Izza Arshad; Naoufel Kraiem; Ahmed Mir; Lioua Kolsi; Ahmad H. Milyani; Mohammed N. Ajour; Hesham A. Alhumade; Aliakbar Karimipour (Case Studies in Thermal Engineering)
In hot and desert regions, buildings have a considerable share in electricity consumption, so supplying electricity in critical hours for building cooling is always challenging for the electricity supply grid. In this numerical study, using sensible and latent-based storage approaches, the goals of peak shaving and load shifting were pursued. The sensible-based approach (first technique) was followed by adding a cold water storage tank which is responsible for cooling the building during critical hours. The tank is charged by the chiller during off-peak hours. The latent-based approach (second technique) was achieved through phase change materials (PCMs) integrated into building envelopes. Owing to using the sensible-based approach, not only was the electricity consumption completely cut during critical hours, but the peak hour was postponed to the early hours of the next day (i.e., load shifting). Based on the results, using the first technique does not necessarily lead to peak shaving. To follow the goal of peak shaving, the use of the second technique is recommended. The simultaneous use of both approaches made the building meet the cooling requirements during critical hours without receiving electricity from the supply grid. Moreover, the building receives up to 54.9 % less electricity from the grid (peak shaving), and simultaneously peak hour was postponed by at least 6 h (load shifting).